Improving Indonesian students' mathematical literacy with brain-based learning: a comparative study of pisa scores - Kandaga, Thesa; Krisnadi, Elang; Nurhayati, Suci; Gusti, Valeria Yekti Kwasaning (Jurnal Konseling dan Pendidikan, 2024)
This research is driven by Indonesia's comparatively low performance in the 2023 PISA assessment, which indicates a significant deficiency in students' capacity to solve literacy-based mathematical problems, largely attributable to the absence of comprehensive, structured guidance. This consequently gives rise to low levels of mathematical literacy, thereby underscoring the necessity for enhanced learning methodologies. The objective of this study is to evaluate the efficacy of the Brain-Based Learning (BBL) model in enhancing students' mathematical literacy abilities in comparison to the traditional learning approach. This study employed a quasi-experimental methodology with an unequal control group design. The research subjects were 72 grade VIII students at SMPN 1 Baleendah, comprising 36 experimental group students (grade VIII K) and 36 control group students (grade VIII L). The data were obtained through mathematical literacy tests and subsequently analysed using descriptive and inferential statistics with the assistance of IBM SPSS 24.0 software. The results of the n-gain analysis indicated that the data were normally distributed with homogeneous variances. The results of the independent sample t-test indicated a statistically significant difference in the improvement of mathematical literacy skills between the two groups, with the BBL group exhibiting a greater degree of improvement than the conventional method. These findings contribute to the scientific literature on the effectiveness of the Brain-Based Learning (BBL) model in addressing low mathematical literacy in Indonesia, with statistically significant improvements. This research provides new insights into the application of brain-based learning models in the Indonesian educational context.